Foliar N⁄ P ratio and nutrient limitation to vegetation growth on Keerqin sandy grassland of North-east China. - Li, L.-J.; Zeng, D.-H.; Yu, Z.-Y.; Fan, Z.-P.; Mao, R.; Peri, Pablo Luis (Wiley, 2022)
To examine whether the critical leaf N ⁄ P ratios (of 14, 16) are valid to test nutrient limitation in the context of semi-arid sandy grasslands, an experiment was conducted on a Keerqin sandy grassland in North-east China to investigate the responses of plant biomass and nutrient concentrations to fertilization. Plant biomass production and leaf nutrient concentrations were measured after five consecutive years of fertilization with N (20 g N m)2 year)1) and ⁄ or P (10 g P2O5 m)2 year)1). Nitrogen fertilization increased the shoot biomass by twofold and consequently the shoot ⁄ root ratio, whereas P fertilization had little effect on either shoot biomass or shoot ⁄ root ratio. Leaf N ⁄ P ratio varied among species with an average of 5Æ6 in the control, while the mean leaf N ⁄ P ratio (7Æ5) under the N fertilization treatment remained below the threshold of 14. Our results suggest that the critical N ⁄ P ratio (14, 16) is not applicable as a test for nutrient limitations in the context of semi-arid, sandy grassland.